Anti-diabetic effect of black ginseng extract by augmentation of AMPK protein activity and upregulation of GLUT2 and GLUT4 expression in db/db mice - Ok-Hwa Kang; Mi-Yae Shon; Ryong Kong; Yun-Soo Seo; Tian Zhou; Do-Yeon Kim; Yeong-Soo Kim; Dong-Yeul Kwon (BMC, 2017)
Abstract Background Black ginseng (Panax ginseng C. A. Meyer), three to nine times-steamed and dried ginseng, has biological and pharmacological activities. In this study, the anti-diabetic effects of the black ginseng ethanol extract (GBG05-FF) in typical type 2 diabetic model db/db mice were investigated. Methods The effect of GBG05-FF in Type 2 diabetic mice was investigated by their blood analysis, biological mechanism analysis, and histological analysis. Results The mice group treated with GBG05-FF showed decreased fasting blood glucose and glucose tolerance compared to that of the nontreated GBG05-FF group. In the blood analysis, GBG05-FF decreased main plasma parameter such as HbA1c, triglyceride, and total-cholesterol levels related to diabetes and improved the expression of genes and protein related to glucose homeostasis and glucose uptake in the liver and muscle. The histological analysis result shows that GBG05-FF decreased lipid accumulation in the liver and damage in the muscle. Moreover, GBG05-FF increased the phosphorylation of the AMPK in the liver and upregulated the expression of GLUT2 in liver and GLUT4 in muscle. Therefore, the mechanisms of GBG05-FF may be related to suppressing gluconeogenesis by activating AMPK in the liver and affecting glucose uptake in surrounding tissues via the upregulation of GLUT2 and GLUT4 expression. Conclusion These findings provided a new insight into the anti-diabetic clinical applications of GBG05-FF and it might play an important role in the development of promising functional foods and drugs from the viewpoint of the chemical composition and biological activities.